PERILAKU KEPEMIMPINAN BIROKRASI DI KANTOR PENELITIAN DAN PENGEMBANGAN (LITBANG) PROVINSI KALIMANTAN BARAT - Unjang E.21108081 (PublikA, Jurnal Ilmu Administrasi Negara, 2012)
AbstractThe purpose of this research are indutified and analyze the behavior of leader attitude in creatingthe condition of work environment. Through this research, I try to describe the behavior of leadersin carry out for the basic needs of his follower, and to describe the behavior of the leaders inproviding guidance his follower in done the work. The method of this reseach is qualitatives andthe result with descriptive. The results showed that, first, the behavior of the leaders success indevelop work condition and that make the follower become comford doing their job. Second,leader also have more attention on the need of follower. Third, the attitude of leade in providingwork quidance more effective and wise. Fouth, leader also applied straight quality and theirfollower in doing their job.Keywords: leadership behavior, public bureaucracy